110k views
1 vote
3(x-2)+7=16 simplified

User ZektorH
by
4.7k points

2 Answers

5 votes
3(x-2)+7=16
Distribute the 3
3x-6+7=16
add like terms: -6+7= 1
3x+1=16
Subtract 1 on both sides
3x=15
Isolate x by dividing by 3
x=5
User Jeff Fischer
by
4.9k points
1 vote

9514 1404 393

Answer:

3x +1 = 16

Explanation:

"Simplified" usually means parentheses are eliminated and like terms are combined.

3(x -2) +7 = 16 . . . . . given

3x -6 +7 = 16 . . . . . . parentheses eliminated using the distributive property

3x +1 = 16 . . . . . . . . . constants are combined (simplified equation)

__

You can solve this in 2 steps:

3x = 15 . . . . subtract 1

x = 5 . . . . . . divide by 3

User Davidcondrey
by
4.5k points